2021
DOI: 10.1111/dth.15076
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous lymphocytic vasculitis after administration of COVID ‐19 mRNA vaccine

Abstract: To date, several individuals have received COVID-19 vaccinations; therefore, the development of adverse skin reactions is expected. We report a peculiar cutaneous eruption post anti-Covid-19 vaccination (BNT162B2/ Pfizer) in a woman without comorbidities, with a previous history of Covid 19 infection. A 51-year-old female patient, in good general health,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
3
7
0
1
Order By: Relevance
“…Previous reported cases of post COVID‐19 vaccine associated reactivated or new onset LCV or IgA vasculitis were seen with either mRNA or inactivated SARS‐CoV‐2 vaccines but none with recombinant corona virus vaccine (Table S1 ). 4 , 7 , 8 , 9 , 10 , 11 In both of our cases, a temporal association between vaccination and LCV could be established with a probable causal relationship in case 1 and definite relationship in case 2. Historically, first LCV episode in case 2 occurred 7 days after vaccination, which was mild with rash limited to ankles, resolving within a week and without any constitutional symptoms.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Previous reported cases of post COVID‐19 vaccine associated reactivated or new onset LCV or IgA vasculitis were seen with either mRNA or inactivated SARS‐CoV‐2 vaccines but none with recombinant corona virus vaccine (Table S1 ). 4 , 7 , 8 , 9 , 10 , 11 In both of our cases, a temporal association between vaccination and LCV could be established with a probable causal relationship in case 1 and definite relationship in case 2. Historically, first LCV episode in case 2 occurred 7 days after vaccination, which was mild with rash limited to ankles, resolving within a week and without any constitutional symptoms.…”
Section: Discussionsupporting
confidence: 53%
“…Dermatological manifestations similar to reported in COVID‐19 infection are now being increasingly seen associated with COVID‐19 vaccination. New onset or reactivation of cutaneous and IgA vasculitis has been observed in handful of cases associated with either messenger ribonucleic acid (mRNA) or inactivated SARS‐CoV‐2 vaccines but none with ChAdOx1 nCoV‐19 corona virus vaccine (recombinant) 4,7–11 . ChAdOx1 nCoV‐19 corona virus vaccine (recombinant) is replication‐deficient chimpanzee adenovirus vector vaccine that encodes SARS‐CoV‐2 Spike glycoprotein which is being extensively used in Indian subcontinent, European, and South American nations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 Only three cases have been reported so far. 7 , 8 , 9 Kharkar et al 8 reported a 31‐year‐old woman with painful purpuric lesions on her legs with pedal edema, one day after her second dose of inactivated viral vaccine (COVAXIN®; Bharat Biotech, Hyderabad, India). RT‐PCR for SARS‐CoV‐2 infection was negative.…”
Section: Resultsmentioning
confidence: 99%
“…Only one had cryoglobulinemia. 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 Nastro et al 21 reported an 84‐year‐old woman, with history of chronic kidney disease and depressive disorder, developed burning pain on the distal part of right leg and foot, followed by ipsilateral multiple non‐confluent purpuric papules and vesicles few hours after she received the first dose of Pfizer‐BioNTech COVID‐19 vaccine. PCR of a skin swab for varicella‐zoster virus (VZV) resulted positive, and VZV IgM and IgG antibodies were positive.…”
Section: Resultsmentioning
confidence: 99%